(untitled) (BIRDEM Medical Journal, 2014)
Aim: To investigate the correlation of maternal blood Hb level and iron stores with neonatal iron status. Methods: A cross sectional analytic study on was conducted on fifty hospitalized pregnant women and their neonates over one year in a teaching hospital in the capital city of Bangladesh. Paired samples (50) of maternal venous and neonatal Women who had no medical complications and had undergone caesarian section were included. Maternal serum and cord hemoglobin concentrations with ferritin values were measured immediately after delivery. Placental weight, birth weight and APGAR scores were recorded. Result: The study involved 50 participants, randomly selected, of whom 10 had normal iron status and others had mild to severe anemia. Our study found no significant correlation of maternal Hb and cord Hb levels. But maternal serum ferritin showed positive correlation with cord ferritin (r=0.94; P<0.001) and with placental weight (r=0.40; p<0.001). Conclusion: Maternal iron deficiency anaemia was strongly associated with lower iron status of newborn DOI: http://dx.doi.org/10.3329/birdem.v4i1.18550 Birdem Med J 2014; 4(1): 27-32